Industrial innovation and parallel accounting developments - Sweeting, R.C.
Via an ongoing research programme, the authors present and discuss changes and developments in accounting techniques in an equally changing manufacturing environment. They stress the importance of top management involvement and support in accounting innovations with extended use of parallel rather than sequential processes of development.
In this paper, we examine parallel accounting developments that have taken place in the late 1980s and early 1990s to complement and support the changing manufacturing environment. As a background to understanding the process of change that has taken place in accounting, we use the industrial innovation model, recognizing that it also has evolved [6]. Material obtained from an ongoing research programme that is aimed at examining the development and deployment of new accounting techniques and practices is presented and discussed. This material suggests that several comparable features of contemporary industrial product innovation are also present in accounting innovation activity. These features include, inter alia, a multidiscipline team involvement and improved dialogue between lead 'users' and 'suppliers'. The improved dialogue can result in useful feedback on new innovation trajectories. The importance of top management support for innovations in accounting cannot be underestimated if the innovations are to be successfully developed, implemented and become 'good currency'. There is evidence that accounting innovations are taking place in a rich yet complex environment of multi-inputs, increased mutual understanding of all the key players and with extended use of parallel rather sequential processes of development. A particular focus of the paper is the way that ideas associated with activity based costing have been widened and deepened to facilitate business process design.
Keywords: Industrial innovation; Parallel accounting